2010
DOI: 10.3109/02699051003789229
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predictors of response to treatment with citalopram in depression secondary to traumatic brain injury

Abstract: Objectives-To determine which serotonergic system-related single nucleotide polymorphisms (SNPs) predicted variation in treatment response to citalopram in depression following a traumatic brain injury (TBI).Methods-Ninety (50 M/40 F, aged 39.9, SD = 18.0 years) post-TBI patients with a major depressive episode (MDE) were recruited into a 6-week open-label study of citalopram (20 mg/ day). Six functional SNPs in genes related to the serotonergic system were examined: serotonin transporter (5HTTLPR including rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 83 publications
(90 reference statements)
6
36
0
1
Order By: Relevance
“…Our results with SSRI are in agreement with those of a previous clinical 6-week study (Lanctôt et al, 2010) treated with an SSRI, showing higher response rates to SSRI in Val/ Val patients. However, our results differ from those of several studies: the 12-week study on a small sample of 32 Caucasian geriatric depressed patients treated with escitalopram (Alexopoulos et al, 2010), the study of El-Hage et al (2014), which focused on 3-week response in both bipolar and MDD patients, the negative 6-week study of Brunoni et al (2013) in a small sample of 120 patients of heterogenous ethnicity, and studies in Asian patients (Choi et al, 2006;Katsuki et al, 2012;Niitsu et al, 2013).…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Our results with SSRI are in agreement with those of a previous clinical 6-week study (Lanctôt et al, 2010) treated with an SSRI, showing higher response rates to SSRI in Val/ Val patients. However, our results differ from those of several studies: the 12-week study on a small sample of 32 Caucasian geriatric depressed patients treated with escitalopram (Alexopoulos et al, 2010), the study of El-Hage et al (2014), which focused on 3-week response in both bipolar and MDD patients, the negative 6-week study of Brunoni et al (2013) in a small sample of 120 patients of heterogenous ethnicity, and studies in Asian patients (Choi et al, 2006;Katsuki et al, 2012;Niitsu et al, 2013).…”
Section: Discussionsupporting
confidence: 96%
“…Some studies suggest an association between the Val66Met polymorphism and response or remission with antidepressant drugs, either in Asian (Choi et al, 2006;Xu et al, 2012;Yoshida et al, 2007; or in Caucasian (Alexopoulos et al, 2010;El-Hage et al, 2015;Lanctôt et al, 2010) patients. However, several studies failed to replicate this association, both in Asian (Ji et al, 2013;Kang et al, 2010;Katsuki et al, 2012;Tsai et al, 2003) and in Caucasian (Brunoni et al, 2013;Domschke et al, 2010;Kocabas et al, 2011;Licinio et al, 2009;Musil et al, 2013;Taylor et al, 2011;Wilkie et al, 2007) patients, especially two 6-month studies (Bukh et al, 2010, Taylor et al, 2011 and the powerful study comprising the STAR-D results (Domschke et al, 2010).…”
mentioning
confidence: 98%
“…BBB disruption in epileptic patients following even mild TBI is not an infrequent observation (Tomkins et al 2011). Mild TBI induces neuropathological insult ranging from white matter damage to long-lasting neurocognitive deficits (Bazarian et al 2006;McAllister et al 2006;Niogi et al 2008), with or without affective disorder symptoms Lanctôt et al 2010;Rapoport et al 2008). Zohar et al (2011), in a mouse model of mild TBI, have observed profound and long-lasting, irreversible cognitive impairments as well as permanent depressive-like behavior.…”
Section: Pathophysiological Consequences Of Tbimentioning
confidence: 97%
“…Folate deficiency has been also associated with Major Depressive Disorder (MDD) presumably because of its impact on neurotransmitter synthesis, which relies on the folate-dependent one-carbon pathway (Mischoulon and Raab, 2007). Moreover, studies showed that low folate levels may delay improvement in antidepressanttreated individuals, whereas folate supplementation may improve response to antidepressant drugs in MDD patients (Farah, 2009; gene has been widely investigated in association with MDD and its treatment with inconclusive findings (Lewis et al, 2006;Gaysina et al, 2008;Lanctot et al, 2010;Lizer et al, 2011;Mischoulon et al, 2012;Jamerson et al, 2013;Wu et al, 2013;Gatt et al, 2015). In particular, the two most commonly studied single nucleotide polymorphisms (SNPs) are rs1801133 (C677T) and rs1801131 (A1298C).…”
Section: Introductionmentioning
confidence: 99%